Japanese cancer screening programs during the COVID-19 pandemic: Changes in participation between 2017-2020. (February 2023) - Machii, Ryoko; Takahashi, Hirokazu
Abstract: Background: The impact of the coronavirus disease 2019 (COVID-19) pandemic on cancer screening participation is a global concern. A national database of screening performance is available in Japan for population-based cancer screening, estimated to cover approximately half of all cancer screenings. Methods: Utilizing the fiscal year (FY) 2017–2020 national database, the number of participants in screenings for gastric cancer (upper gastrointestinal [UGI] series or endoscopy), colorectal cancer (fecal occult blood test), lung cancer (chest X-ray), breast cancer (mammography), and cervical cancer (Pap smear) were identified. The percent change in the number of participants was calculated. Results: Compared with the pre-pandemic period (FY 2017–2019), in percentage terms FY 2020 recorded the largest decline in gastric cancer UGI series (2.82 million to 1.91 million, percent change was −32.2 %), followed by screening for breast cancer (3.10 million to 2.57 million, percent change was −17.2 %), lung cancer (7.92 million to 6.59 million, percent change was −16.7 %), colorectal cancer (8.42 million to 7.30 million, percent change was −13.4 %), cervical cancer (4.26 million to 3.77 million, percent change was −11.6 %), and gastric cancer via endoscopy (1.02 million to 0.93 million, percent change was −9.0 %). Conclusion: The number of participants in population-based screenings in Japan decreased by approximately 10–30 % during the pandemic. The impact of these declines on cancer detection or mortality should be carefully monitored. Highlights: COVID-19 has been reported to affect cancer screening participation. % change in screening participation in Japan before/during COVID-19 was calculated. Participants in population-based screening decreased by 10–30 % during the pandemic. Impact of these declines on cancer detection or mortality should be monitored. In the post COVID era, it will be important to monitor cancer screening attendance.